Relationship between QT dispersion and biochemical parameters in Behçet’s disease - Altuntaş, Emine; Nazik, Hülya; Gül, Feride Çoban; Demir, Betul (My University, 2019)
Objective: Ventricular arrhythmia and sudden cardiac death are more frequently in Behçet’s disease (BD) patients than normal population. Therefore in this study it was aimed to find out relationship among QT dispersion, Behçet’s disease and biochemical parameters related with disease.Material and Method: The study consisted of 35 patients which diagnosed Behçet’s disease (BD) according to international diagnose criteria and 47 healthy controls which were matched with regard to age and gender. 12-channel surface electrocardiography (ECG) was performed to all participants. QT distances, corrected QT (QTc) distances which is calculated by using Bazett formula were calculated. The longest QT, and the shortest QT, the longest QTc, the shortest QTc were found in the ECG. Afterwards QTd and QTcd were calculated. Blood samples were taken from participants after 12 hours fasting.Findings: The groups were compared in terms of the longest QT-QTc, the shortest QT-QTc, QTd, QTcd. It was seen that there was meaningful difference in terms of the longest QT and QTc (respectively p; 0.004; 0.018). Mean platelet volume (MPV) and albumin were higher in control group while erythrocyte sedimentation rate (ESR) was higher in BH group (respectively p; 0.000; 0,000; 0,002). Additionally there was negative correlation among the longest QT-QTc and ESR, albumin, but there was established positive correlation between the longest QT -QTc and MPV. Statistical results were presented in table 2-3-4.Conclusion: Consequently in this study, it was established that the longest QT and QTc was increased and there was relationship between biochemical parameters and the longest QT-QTc.
Keywords: Genel ve Dahili Tıp; Klinik Nöroloji; Kalp ve Kalp Damar Sistemi